2020
DOI: 10.1108/caer-06-2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous choice in the demand for agriculture credit in China: results from an in-the-field choice experiment

Abstract: PurposeIn this study, the authors examined demand-side credit in rural China with the aims of understanding attribute preferences and the willingness of farmers to pay for credit.Design/methodology/approachThe authors implemented an in-the-field discrete choice experiment (DCE) using a D-optimal block (6 × 9 × 3) design applied to 420 farm households across five Chinese provinces (Shandong, Sichuan, Shaanxi, Jiangsu and Henan) in the summer and fall of 2018. The DCE included six attributes including the intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
1
15
2
Order By: Relevance
“…Due to the different industrial structures of different provinces and cities, agriculture accounts for a relatively low proportion of the economic composition of municipalities directly under the central government. With reference to the treatment methods of the existing literature, municipalities directly under the central government were removed for the robustness test [ 58 ]. In Table 8 , The coefficient of the core explanatory variable in robustness test is 4.419, which significant at the 1% level.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the different industrial structures of different provinces and cities, agriculture accounts for a relatively low proportion of the economic composition of municipalities directly under the central government. With reference to the treatment methods of the existing literature, municipalities directly under the central government were removed for the robustness test [ 58 ]. In Table 8 , The coefficient of the core explanatory variable in robustness test is 4.419, which significant at the 1% level.…”
Section: Resultsmentioning
confidence: 99%
“…The work of Kong et al . (2020) showed that the credit demand curve is downward sloping with varying elasticity across rural China.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this study, we assume, apart from the risk incurred by the agricultural sector, that financial institutions do not have a clear knowledge on the financial needs of farmers which are necessary to stimulate productivity and economic growth. Therefore, understanding the profiles of credit matching farmers' preferences and the informational problems that exist between lenders and borrowers is important to guide the development of agricultural financial policies (Cao et al ., 2016; Kong et al ., 2020). Given the importance of credit for improving agricultural productivity and the main role of this sector in reducing poverty and food insecurity, this study aims to answer the following questions: what are the intrinsic characteristics that shape the demand for credit in rural Benin?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the active involvement of the rural finance, the absolute poverty that has been plaguing the rural areas in China has been successfully solved, and the focus of finance itself on rural services has moved from poverty alleviation to a higher level, revitalization . Although some success in the development of the rural finance in China, there is still a contradiction between insufficient effective supply and diversified demand, especially in the post-COVID-19 era (Kong et al , 2020; Jiang et al , 2020).…”
Section: Introductionmentioning
confidence: 99%